Preparation, Modification, and Application of Hollow Gold Nanospheres. (21st October 2015) - Ren, Qiong-Qiong; Bai, Ling-Yu; Zhang, Xiao-Shuai; Ma, Zhi-Ya; Liu, Bo; Zhao, Yuan-Di; Cao, Yuan-Cheng
Abstract : Hollow gold nanospheres (HGNs) have great potential applications in biological sensing, biomedical imaging, photothermal therapy, and drug delivery due to their unique localized surface plasmon resonance (LSPR) feature, easy modification, good biocompatibility, and excellent photothermal conversion properties. In this review, the latest developments of HGNs in biosensing, bioimaging, photothermal therapy, and drug delivery are summarized, the synthesis methods, surface modification and bioconjugation of HGNs are also covered in this summary.